Role of prophylactic antibiotics in preventing postoperative wound infection in clean surgeries: a comparative study - Ferdousi, Tamanna; Noor-ul Ferdous, Kazi M.; Sultana, Sadia; Huq, Umama (International Journal of Contemporary Pediatrics, 2025)
Background: The role of prophylactic antibiotics in clean surgeries remains controversial in the pediatric population. Despite guidelines discouraging routine use, many surgeons prescribe them due to concerns regarding surgical site infections (SSIs). This study evaluated whether perioperative prophylactic antibiotics reduce postoperative wound infection in pediatric clean surgeries and assessed their cost implications. Methods: This prospective, comparative interventional study was conducted at Bangladesh Shishu Hospital and Institute (Formar Dhaka Shishu Hospital) from March 2021 to September 2023. A total of 130 pediatric patients undergoing clean surgical procedures were randomly allocated into two groups: Group A (n=65) received a single-dose prophylactic antibiotic, and Group B (n=65) did not. Patients were followed up on the 3rd, 7th, and 30th postoperative days for signs of infection. Statistical analyses were performed using SPSS version 23.0, with a p value <0.05 considered significant. Results: The mean age was 35.01±32.925 months in group A and 39.70±32.42 months in group B. The mean treatment cost was slightly higher in the antibiotic group (8526.25±900.10 BDT) than in the non-antibiotic group (8335.75±700.20 BDT). On the 7th postoperative day, one patient (1.5%) in the antibiotic group developed wound redness, swelling, serous discharge, and tenderness. No infection was recorded in the non-antibiotic group. By the 30th postoperative day, all the patients were healthy. Conclusion: Prophylactic antibiotics are unnecessary in pediatric clean surgeries and do not reduce postoperative wound infections. Avoiding their use may reduce healthcare costs and support antimicrobial stewardship, without compromising patient outcomes.